Laboratory and Field Testbed Evaluation of the Performance of Recycled Asphalt Mixture Using High-Penetration Asphalt - Sang-Yum Lee; Young-Min Kim; Tri Ho Minh Le (Buildings, 2023)
The application of recycled asphalt pavement (RAP) on a large scale is highly promoted to meet the current needs of carbon neutrality and sustainable development purposes. However, a majority of RAP mixture productions are currently relying on the restoring effects provided by the rejuvenators. Therefore, the study focuses on the feasibility of using high penetration asphalt binder (HPAB) in RAP mixture as a replacement for conventional rejuvenators. In this study, a recycled asphalt pavement mixture containing HPAB (RAP-H) was developed to resolve the cracking issue of RAP pavement in winter seasons owing to the rigid behavior of aged binders. To verify the applicability of the RAP-H mixture, the results of the quality standard test and mechanical performance test were compared with the reference RAP mixture having rejuvenator (RAP-R). Through the fatigue cracking test, by using Overlay Tester (OT) device, it was found that all specimens did not reach 93% load reduction after 1000 OT cycles, indicating a satisfied stress-bearing capacity. Additionally, the highest dynamic modulus of 27,275 MPa was found in the modified HPAB mixture, and this result is 4.4% higher than that of the reference mix. In the full-scale testbed, the long-term field applicability of the proposed approach was verified through field test construction. The measurement in practice reveals that the elastic modulus of RAP-H back-calculated from the FWD (Falling Weight Deflectometer) test is increased by more than 50% compared to RAP-R, which resulted in excellent performance characteristics of the HPAB pavement layer. In addition to the efficiency in the surface layer, an improved elastic modulus of the sub-base and subgrade layers in the HPAB section was found to be at 28.6% and 19.5%, respectively, compared to the RAP-R mix. In general, the performance of RAP-H satisfied all of the domestic and international quality and performance standards. The field test results confirmed the possibility of field application by showing performance higher than conventional recycled asphalt pavement.